CCR9 expression defines tolerogenic plasmacytoid dendritic cells capable of suppressing acute graft-versus-host disease - Hadeiba, Husein (2008)
Dendritic cells are professional antigen-presenting cells that play a key role in the regulation of immune responses. Here we characterize a unique subset of tolerogenic DCs that expressed the chemokine receptor CCR9 and migrated to the CCR9 ligand CCL25, a chemokine implicated in T cell and DC homing to the gut. CCR9(+) DCs were of the plasmacytoid DC lineage, possessed an immature phenotype and rapidly downregulated CCR9 in response to maturation-inducing pDC-restricted Toll-like receptor ligands. CCR9(+) pDCs were potent inducers of regulatory T cell function and suppressed antigen-specific immune responses both in vitro and in vivo, including inhibition of acute graft-versus-host disease induced by allogeneic CD4(+) donor T cells in irradiated recipients. The results identify a highly immunosuppressive population of pDCs present in lymphoid tissues.